2018
DOI: 10.1051/e3sconf/20187100012
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of cement slurries modified by silica nanostructures applied in drilling industry

Abstract: The most important purpose of cementing boreholes is to counteract the inflow of deep-seated waters into productive levels of oil and gas-bearing rocks. The increasing requirements regarding the properties of cement grout and cement stone enforces the search for unconventional solutions and materials that will provide a resolved improvement in their properties and resistance to temperature and chemical factors in difficult geological and reservoir conditions. Therefore, the number of binding materials that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Besides, the crystallinity size from XRD analysis of SiO 2 is smaller than the particle size obtained from SEM, which is attributed to the particle of SiO 2 having many crystal configurations. Further, Piklowska 52 reported that silica with nano‐size affects the drilling properties, which can contribute to the desired wellbore in drilling. In short, the unique structure of SiO 2 has been proven with the SEM and XRD profiles obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the crystallinity size from XRD analysis of SiO 2 is smaller than the particle size obtained from SEM, which is attributed to the particle of SiO 2 having many crystal configurations. Further, Piklowska 52 reported that silica with nano‐size affects the drilling properties, which can contribute to the desired wellbore in drilling. In short, the unique structure of SiO 2 has been proven with the SEM and XRD profiles obtained.…”
Section: Resultsmentioning
confidence: 99%